Sites of Girlhood. Issue 2 (1st June 2021) - Isselhardt, Tiffany Rhoades
Abstract : Where are the girls who made history? What evidence have they left behind? Are there places and spaces that bear witness to their memory? Girl Museum was founded in 2009 to address these questions, among many others. Established by art historian Ashley E. Remer, whose work revealed that most, if not all, museums never explicitly discuss or center girls and girlhood, Girl Museum was envisioned as a virtual space dedicated to researching, analyzing, and interpreting girl culture across time and space. Over its first ten years, we produced a wide range of art in historical and cultural exhibitions that explored conceptions of girlhood and the direct experiences of girls in the past and present. Led by an Advisory Board of scholars and entirely reliant on volunteers and donations, we grew from a small website into a complex virtual museum of exhibitions, projects, and programs that welcomes an average 50, 000 visitors per year from around the world.